Hitting time for random walks on the Sierpinski network and the half Sierpinski network - Sun, Yu; Liu, Xiaobei; Li, Xiaoyan (Frontiers in Physics, 2022)
We consider the unbiased random walk on the Sierpinski Network (Sn ◦ N) and the Half Sierpinski Network (HSn ◦ N). Different from existed works on the Sierpinski Gasket, the Sn ◦ N is generated by the nested method and the HSn ◦ N is the half of the Sn ◦ N based on the vertical cutting of the symmetry axis. We study the hitting time on the Sn ◦ N and HSn ◦ N. According to the complete symmetry and structural properties of the Sn ◦ N, we derive the exact expressions of the hitting time on the nth generation Sn ◦ N and HSn ◦ N. The curves of the hitting time for two networks are almost consistent when n is large enough. The result indicates that the diffusion efficiency of the HSn ◦ N has not changed greatly compared with the Sn ◦ N at large scale.